Mathematical beliefs and mathematics anxiety among pre service elementary school teachers in East Kalimantan, Indonesia - Suci Yuniarti (2014)
The study investigated the differences in mathematical beliefs and mathematics anxiety according to gender and years of study, the relationship between mathematical beliefs and mathematics anxiety, and the influence of mathematical beliefs on mathematics anxiety among pre service elementary school teachers in East Kalimantan, Indonesia. This study applied quantitative approach using survey research. The questionnaires were used to gain the data. The sample of this study was 374 pre service elementary school teachers from the elementary school teacher education departments in public universities in East Kalimantan. The data obtained from the questionnaire used in the study were analyzed via SPSS 21.0. Results of descriptive statistics showed that most of pre service elementary school teachers in East Kalimantan were under the moderate category of mathematical beliefs and mathematics anxiety. However, some pre service elementary school teachers still had low mathematical beliefs and high mathematics anxiety. The findings showed that there were no significant differences in mathematical beliefs and mathematics anxiety according to gender. In addition, there was no significant difference in mathematical beliefs according to year of study however there was significant difference on mathematics anxiety according to year of study. A small negative significant correlation between mathematical beliefs and mathematics anxiety was found. The study suggested that mathematical beliefs could predict mathematics anxiety to a small extent. Implications for this study were discussed practically and theoretically.